Fiscal Restraint, Demographic Change, and Social Services in Israel, 1985-1987, and Application of the Methodology to Latin America. (IMF Working Papers; Working Paper, 1988)
The paper analyzes the development of government social expenditure during the economic stabilization period, with specific reference to the changing needs for such expenditure arising from the change in Israel's demographic structure. The results reveal a real cut in direct services. The implicit strategy applied a mere restraint, for some two to three years, with real erosion in services arising from the growth in the size of beneficiary groups. This strategy proved attainable, even though it took more time than an alternative shock-like strategy that would have had little, if any, chance of being implemented. A partial application to six Latin American countries shows that even though the increase of the elderly dependency ratio is more than offset by the declining child-dependency ratio, there will be an overall increase in dependency-related expenditure.